Morton’s neuroma. Diagnostic Imaging - Hernández de la Peña, César; Vega González, Maria Luisa (Revista Internacional de Ciencias Podológicas, 2010)
A review is made of the symptoms, diagnosis and treatment of metatarsal pain due to Morton’s neuroma with special emphasis on the semiology and utility of techniques such as the MR and ultrasound.
Keywords: Interdigital neuroma; Metatarsal pain; MR imaging; Ultrasound imaging